Implementasi Landasan Filosofis – Teleologis Pendidikan Islam Dalam Membangun Pendidikan Karakter (Telaah Surat Ali Imran Ayat 79) - Badriah, Laelatul (Universitas Alma Ata, 2017)
Education is a necessity for every human being, education has the task to form the character, both the character of educators and the character of learners. Al Qur'an letter of Imam Ali 79 paragraph emphasizes the formation of rabbani human beings who will form human beings who love science, love to learn and nagging amar ma'ruf nahi munkar. This review is important to provide an overview of the importance of Islamic education in character building. Therefore, this study can provide a new color for the change of paradigm of Islamic education in conducting academic and non academic activities in an effort to form the character from an early age. So that it can reach the rabbani man in accordance with the Qur'an letter of Imran Ali 79 paragraph and can be implemented in the Islamic education practice both formal and non formal.Keyword: Character Education, Insan Rabbani, Philosophical Foundation - Teleologis